Proton beam therapy delivered using pencil beam scanning vs. passive scattering/uniform scanning for localized prostate cancer: Comparative toxicity analysis of PCG 001-09. (November 2019) - Mishra, Mark V.; Khairnar, Rahul; Bentzen, Søren M.; Larson, Gary; Tsai, Henry; Sinesi, Christopher; Vargas, Carlos; Laramore, George; Rossi, Carl; Rosen, Lane; Zhu, Mingyao; Hartsell, William
Highlights: Benefits of proton beam therapy for treatment of prostate cancer are unknown. Data comparing pencil beam vs. passive scatter/uniform scanning protons are limited. Significant differences in acute toxicity between proton modalities were observed. Future studies evaluating differences between the two proton modalities are needed. Abstract: Background and purpose: Patient-level benefits of proton beam therapy (PBT) relative to photon therapy for prostate cancer (PC) continue to be the focus of debate. Although trials comparing the two modalities are underway, most are being conducted using "conventional" PBT (passive scattering/uniform scanning [PS/US]) rather than pencil beam scanning (PBS). The dosimetric benefits of PBS are well-known, but comparative data are limited. This analysis compares PBS toxicity rates with those of PS/US in a prospective multicenter registry. Methods: We evaluated acute/late gastrointestinal (GI) and genitourinary (GU) toxicity rates for men with low-to-intermediate risk PC enrolled in PCG 001-09. Acute toxicities with the two techniques were compared using χ 2 tests, and the cumulative incidence methods for late toxicity. Multivariable analyses (MVAs) for acute toxicity were performed using logistic regression, and cox proportional hazards models for late toxicity. Results: Patients were treated using PS/US (n = 1105) or PBS (n = 238). Acute grade ≥2 GI toxicity in PBS did not significantly differ from that with PS/US (2.9% and 2.1%, respectively; P = 0.47). Acute grade ≥2 GU toxicity was significantly higher with PBS (21.9% and 15.1%; P < 0.01). In MVA, PBS was significantly associated with increased acute grade ≥2 GU toxicity (RR = 1.57, p < 0.001). Late grade ≥2 GI and GU toxicities did not differ significantly between groups. Conclusions: This is the first multi-institutional comparative effectiveness evaluation of PBT techniques in PC. Differences in acute GU toxicity warrant further evaluation, and highlight the urgent need for prospective data using PBT.